Physical attributes of the soil of urban forests as environmental indicators of environmental degradation - Rocha, Gabriela Manente; Garcia, Joice Machado; Silva, Alessandra Leite da [UNESP]; Longo, Regina Marcia (Centro Pesquisas Florestais, Ufsm, 2020)
The lack of urban planning has led to a disorderly growth in cities and to social and environmental problems such as lack of basic sanitation, water, air and soil pollution, deforestation, among others and also the fragmentation of natural ecosystems. In this context, it is possible to observe, in urban areas, a smaller and increasingly degraded number of forest fragments, especially on their edges, due to the physical alteration of the soils in these places, among other factors of degradation. Therefore, the present study aimed to analyze the physical degradation of the soil in the border areas of two forest fragments located in 'Ribeirao Anhumas' Hydrographic Basin, in Campinas, Sao Paulo state. To do so, the physical indexes of the soils, in addition to the Leaf Area Index (LAI) and the Soil Reddening Index (SRI) were evaluated. The samples were collected at equidistant points between 70 and 80 meters and 20 meters from the edge in each fragment of interest. Along with the results obtained, the Principal Components Analysis (PCA) was carried out in order to identify whether there are correlations between the analyzed indicators. Physical analyzes of the soil indicated that both remnants are in an advanced stage of degradation. One of them, however, presented results with greater variations in all the analyzed physical parameters. Although no correlation has been identified between the physical indices, LAI and SRI, the parameters are efficient in the analysis and identification of the soil degradation, and the results contribute to the establishment of a proposal for the recovery of these areas.
Keywords: Ribeirao Anhumas Basin; Physical Parameters of the Soil; Soil degradation; Urban Forest Fragments